Peran Regulasi Diri terhadap Pencegahan Perilaku Seksual Berisiko pada Remaja: A Systematic Review - Lestari, Wahyu Agustin Eka; Indarwati, Retno; Krisnana, Ilya (BRILIANT: Jurnal Riset dan Konseptual, 2023)
Introduction: The inability of adolescents to control themselves causes adolescents to have low self-regulation and causes several serious problems such as sexually transmitted diseases (STDs), disability and death in adolescents. This review study aimed to identify the role of self-regulation as an effort to prevent sexual behavior in adolescents. Method: A systematic review using 4 databases (Scopus, ScienceDirect, PubMed and Web of Science) published in the last 6 years (2017-2022). Results: Eight articles were selected in the final review. All articles mention the role of self-regulation in adolescents. The role is to control themselves, the environment and behavior so that adolescents who have good self-regulation will be able to prevent sexual behavior. Conclusion: Self-regulation is an individual's ability to regulate emotions, thoughts and behavior to achieve a goal. Adolescents who have higher self-regulation and greater growth of self-regulation will decrease the likelihood of engaging in sexual risk-taking behavior in young adulthood